Spatiotemporal Dynamics of El Niño Modoki Impacts on East Java Rainfall Using EOF, BIRCH Clustering, and Wavelet Coherence - Diah Ariefianty; Agung Budi Susanto; Arya Adhyaksa Waskita (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2026)
El Niño Modoki is a variation of El Niño characterized by sea-surface-temperature warming in the central Pacific, flanked by cooling in the eastern and western Pacific, and can influence rainfall patterns in Indonesia, particularly in East Java. This region was selected because it is one of Indonesia’s major food-producing areas, has high rainfall variability, and remains highly vulnerable to drought. This study aimed to analyze the impact of El Niño Modoki on monthly rainfall anomalies in East Java during 1991–2024. The data consisted of the El Niño Modoki Index (EMI) and monthly gridded rainfall data. The analytical methods included rainfall-anomaly calculation, Pearson correlation, Empirical Orthogonal Function (EOF), BIRCH clustering, Wavelet Coherence (WTC), and composite analysis. BIRCH clustering based on the first three EOF modes formed four rainfall-pattern clusters in East Java. WTC analysis showed that the relationship between EMI and rainfall was more dominant at interannual periods of approximately 1–4 years. Composite analysis indicated that El Niño Modoki reduced rainfall in East Java starting from the JJA period and became stronger and more spatially extensive during ASO. Overall, the impact of El Niño Modoki on East Java rainfall was spatial, seasonal, dynamic, and non-homogeneous across regions. These findings provide preliminary information for drought mitigation, water-resource management, and climate early-warning strengthening in East Java.